THE INFLUENCE OF DIGITAL MARKETING, FACILITIES AND TOURIST ATTRACTIONS ON THE INTEREST IN RETURNING TO UJUNG SUSO BEACH, BURAU DISTRICT, LUWU TIMUR REGENCY - Dwiyanti, Aulia; Maszudi, Edi; Rizkiyah Hasbi, Andi (JURNAL EKBIS, 2025)
This study aims to determine the effect of digital marketing, facilities, and attractions on the interest in revisiting Ujung Suso Beach, Mabonta Village, Burau District, East Luwu Regency. The sample taken was 261 visitors who had visited Ujung Suso Beach. The data collection technique used a questionnaire via a Google form. The method used in this study is quantitative with data analysis techniques processed with SPSS 25 tested with the T test and F test. The results of the study showed (1) Digital Marketing did not have a significant effect on the interest in revisiting, (2) Facilities did not affect the interest in revisiting, (3) Attractions had a significant effect on the interest in revisiting, (4) Digital Marketing, Facilities and Attractions simultaneously did not have a positive and significant effect.